Household War : How Americans Lived and Fought the Civil War - Whites, LeeAnn; Frank, Lisa Tendrich (Book collections on Project MUSE., 2019)
"Household War is a collection of essays that explores the Civil War through the household. According to the editors, the household served as 'the basic building block for American politics, economics, and social relations.' As such, the scholars of this volume make the case that the Civil War can be understood as a revolutionary moment in the transformation of the household order. From this vantage point, they look at the interplay of family and politics, studying the ways in which the Civil War shaped and was shaped by the American household. The volume offers a unique approach to the study of the Civil War that allows an inclusive examination of how the war 'flowed from, required, and ... resulted in the restructuring of the household' between regions and those enslaved and free. This volume seeks to address how households redefined and reordered themselves as a result of the changes stemming from the Civil War. Scholars of this volume provide compelling histories of the myriad ways in which the household played a central role during an era of social upheaval and transformation"--